PERILAKU SENYAWA POLYCYCLIC AROMATIC HYDROCARBONS (PAH) YANG TERKANDUNG DI DALAM PRODUCED WATER INDUSTRI MINYAK DI KOMPARTEMEN AIR DAN SEDIMEN LINGKUNGAN PERAIRAN ASIN - Mindriany Syafila (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2009)
Polycyclic Aromatic Hydrocarbons (PAHs) are ubiquitous pollutants formed from both natural and anthropogenic sources. Produced water of crude oil industries contains PAHs, which in high concentrations could pollute the environment. Saline water environment model used in this research was an aerobic reactor which contains sediment collected from the estuary of Mahakam River. The sediment bacteria were first activated by glucose and toluene before it was exposed to the PAHs compound. Three PAHs compounds observed were naphthalene, anthracene, and phenanthrene. The result showed that it was difficult to determine the PAH degradation rate in the water compartment, because the PAHs were volatile and easily deposited. The degradation rate of naphthalene in the sediment compartment was the highest when compared to anthracene and phenanthrene. Furthermore, phenanthrene was the most undegradable compound.